Odpowiedzi

  • Użytkownik Zadane
2010-02-10T15:47:52+01:00
A) x+x=2x
b) x+3x=4x
c)x+0.5x=1,5x
d)1,2x+x=2,2x
e)5x+2x=7x
f)3x+0.6x=3,6x
g)0.6+1.2x=1,8x
h)x-0.6x=0,4x
i)x-0.85x=0,15x
j)5x-x=4x
k)3x-0.5x=2,5x
l)1,8x-1,2x=0,6x
ł)20x-10,5x=9,5x
m)-5x+x=-4x
n)-2x-3x=-5x
o)5x-(-x)=6x
ó)-10x-(-x) =11x
1 4 1
2010-02-10T15:50:02+01:00
A) x+x=2x
b) x+3x=4x
c)x+0.5x=1,5x
d)1,2x+x=2,2x
e)5x+2x=7x
f)3x+0.6x=3,6x
g)0.6+1.2x
h)x-0.6x=0.4x
i)x-0.85x=0.15x
j)5x-x=4x
k)3x-0.5x=2,5x
l)1,8x-1,2x=0.gx
ł)20x-10,5x=9.5x
m)-5x+x=-4x
n)-2x-3x=-5x
o)5x-(-x)=6x
ó)-10x-(-x) =-9x
2010-02-10T15:52:55+01:00
A) 2x
b) 4x
c) 1,5 x
d) 2,2 x
e) 7x
f) 3.6 x
g) o,6 + 1,2 x
h)0,4 x
i) 0.15 x
j) 4x
k) 2,5 x
l)0,6 x
ł)9,5 x
m) -4x
n) -5x
o)6x
ó) -9x